Problems and Prospects of Accounting Management in the Digital Economy - A. U. Panakhov (Учёт. Анализ. Аудит)
There is an active digitalization of the collecting processes, consolidating and analyzing business data in the modern economy. Against this background, many classical problems of managerial accounting still remain unresolved, among which the selection of cost objects, the search for optimal methods for calculating costs, and the integration of various types and levels of accounting among themselves. The goal of the paper is to reveal key features of management accounting development in modern enterprises. The methodological basis of the work is a systematic approach, reflected in the idea of management accounting as a multi-level system that combines methodological, organizational and infrastructural aspect. The result of the study is the disclosure of the imbalance problems associated with increased attention to higher levels of management accounting without deepening the study of lower levels of business data. There are proposed the following directions of management accounting development: further division of accounting objects; expanding the possibilities of solving the problems of calculating costs due to modern technologies; integration of cost accounting with process models, which maintained in companies today outside the framework of accounting management. The results may be of interest to researchers, practitioners in the financial management and IT fields